The Urgency and Direction of Environmental Insurance in Indonesia: A Constitutional Law Perspective - Teguh, Pri Pambudi; Mustakim, Mustakim; Chansrakaeo, Ruetaitip (Faculty of Law, Jambi University, 2026)
A recent decision of the Indonesian Constitutionalourt’shas significant implications for the principle of utmost good faith in insurance practice, particularly by strengthening reciprocal duties between insurers and insured parties and restricting unilateral policy termination. This has implications for various types of insurance, including environmental insurance. This research focuses on analyzing the urgency and orientation of environmental insurance in Indonesia after Constitutional Court Decision Number 83/PUU-XXII/2024. This normative legal research confirms that the urgency of specific regulations on environmental insurance in Indonesia is increasingly pressing, particularly due to large-scale ecosystem degradation caused by industrial activities, mining exploitation, and other high-risk sectors. This study offers a novel regulatory framework for environmental insurance in Indonesia by linking the Indonesian Constitutional Court’s reinterpretation of Article 251 of the Commercial Code (KUHD) with the future legal design of Environmental Liability Insurance (ELI). The research finds that the Court’s approach to contractual fairness requires environmental insurance regulation to shift toward stronger consumer protection and procedural safeguards. It argues that future regulations should institutionalize reciprocal utmost good faith obligations, prevent unilateral policy cancellation, and require objective proof of material environmental risk through due process mechanisms. This study also proposes expanding mandatory ELI beyond the limited B3 waste regime to other high-risk sectors such as mining, plantations, chemical industries, and infrastructure projects. This contributes by integrating constitutional doctrine into environmental insurance governance